Kamenje vredno več kot les - Cimperšek, Mitja (Gozdarski vestnik, 2014)
Knowledge of the non-wood forest gifts is important for history of forestry, for they used to be more important than wood. In this article we describe use of diverse rocks in geologically varied Upper Obsotelje in the past and today.
Keywords: forestry; gozdarstvo; kamnine; brus; mlin; okras; cestogradnja; Zgornje Obsotelje